Path analysis of factors that influence students in choosing a study program to get to their dream job - Syafril, Syafril; Selvanus, Selvanus; As-Syahri, Hidayatullah; Susanto, Hari; Wahyudi, Wahyudi; Syaifullah, Syaifullah (Jurnal Ekonomi, 2024)
This research aims to analyze the factors that influence students in choosing a study program or major to lead to their dream job. This research is quantitative descriptive research using a survey method. Primary research data was obtained using Google Form with Likert scale questionnaire questions. Data analysis uses path diagrams with linear regression and Sobel test with the SPSS 21 application. The research results show that interest factors, financial factors, career factors and family factors do not have a significant effect on the study program. The results of this research show that interest factors, financial factors, career factors, family factors and study programs also do not have a significant effect on dream work. Apart from that, the results of this research show that interest factors, financial factors, career factors and family factors simultaneously have a significant influence on study programs and dream jobs. The results of this study indicate that the factors that influence students do not significantly mediate the relationship between study programs and dream jobs.